Solubility and Dissolution Rate Enhancement of Bilastine by Solid Dispersion Technique - Mariam Hamid Ali; Kawther Khalid Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2025)
Bilastine (BLS) is non-sedating new-brand H1 antihistamine that has selective peripheral effects, the drug has a problem of an insufficient aqueous solubility and accordingly low dissolution rate, and low bioavailability. Solid dispersion (SD) is one of the most effective techniques for improving the solubility and the dissolution rate of poorly soluble drugs by the dispersion of drug within an inert hydrophilic carrier. The aim of this study is to increase the solubility and dissolution rate of the BLS using SD technique. Twenty-nine BLS SD formulas were prepared using different carrier polymers include Pluronic 407 (Poloxamer407), Poloxamer188, Urea, Polyethylene glycol 6000 (PEG6000) and Polyvinylpyrrolidone (PVP K30) and employing two different preparation methods (solvent evaporation and kneading method) at different drug: polymer ratios (1:1 ,1:3,1:5,1:10,1:15). The prepared SD formulas were evaluated for their percent yield, drug content, aqueous solubility, dissolution rate, PXRD, and FTIR. The SD technique successfully improved the solubility and dissolution rate of BLS. The improvement was largely dependent on the polymer type and drug: polymer ratio. The solubility improvement using different polymers was in the following order: PVP K30> PLX188> PEG6000> Urea> PLX407. The solid dispersion formula that showed the best outcomes in terms of dissolution improvement was prepared using the solvent evaporation technique employing PVP K30 at ratio of drug: polymer of 1:15. The optimized formula showed 10.2 folds increment in the solubility compared to pure BLS. It can be concluded that the SD technique can successfully improve the solubility and dissolution rate by solvent evaporation method with careful selection of the carrier polymer and drug: polymer ratio.